Lower limb muscle coactivation levels in healthy younger and older adults during functional dual-task gait - Hallal, Camilla Zamfolini [UNESP]; Marques, Nise Ribeiro [UNESP]; Vieira, Edgar Ramos; Brunt, Denis; Spinoso, Deborah Hebling [UNESP]; Castro, Alex [UNESP]; Cardozo, Adalgiso Coscrato [UNESP]; Gonçalves, Mauro [UNESP] (FapUNIFESP (SciELO), 2013)
The purpose of this study was to investigate the influence of daily cognitive task on stiffness of old and young female adults during the gait. The study included 17 physically active younger and 18 older women, with low risk of falls. The volunteers were asked to walk on the treadmill at two different gait conditions: normal gait and functional dual-task gait. The electromyographic signals were collected of the lower limb muscles. The percentage of coactivation for the tibialis anterior/gastrocnemius lateralis and tibialis anterior/soleus were significantly higher in elderly than in younger in the normal gait and dual-task gait. Our results suggest that the elderly have a greater stiffness in the ankle joint during gait normal and daily dual task gait. Thus, we conclude that challenging cognitively situations during the gait may increase the risk of falls in this population.
Keywords: Coactivation; Elderly; Falls; Gait